Wack! Art and the feminist revolution - Butler, Cornelia; Kirshner, Judith Russi; Lord, Catherine; Meskimmon, Marsha; Meyer, Richard; Molesworth, Helen; Phelan, Peggy; Richard, Nelly; Smith, Valérie; Solomon-Godeau, Abigail; Sorkin, Jenny; The Museum of Contemporary Art, Los Angeles; et al. (Cambridge : The MIT press, 2007)
Abakanowicz, Magdalena ; Abramovic, Marina ; Accardi, Carla ; Akerman, Chantal ; Almeida, Helena ; Andrade, Sonia ; Antin, Eleanor ; Baca, Judith F. ; Bauermeister, Mary ; Benglis, Lynda ; Bourgeois, Louise ; Berwick Street Film Collective ; Billops, Camille ; Birnbaum, Dara ; et al.
The Museum of Contemporary Art, Los Angeles, 4 March - 16 July 2007 / National Museum of Women in the Arts, Washington D.C., 21 September - 16 December 2007 / P.S.1 Contemporary Art Center, New York, February - June 2008 / Vancouver Art Gallery, Vancouver, 4 October 2008 - 18 January 2009
kunstcatalogus